Repositioning metformin and propranolol for colorectal and triple negative breast cancers treatment - Anselmino, Luciano (2021)
Fil: Fil: Anselmino, L. E. Universidad Nacional de Rosario. Facultad de Ciencias Médicas. Instituto de Inmunología Clínica y Experimental de Rosario (IDICER-CONICET); Argentina.